Physical fragility syndrome and linguistic abilities in adults: An exploratory study - Otero-Montoto, Tania; Durán-Bouza, Montserrat (Revista de Investigación en Logopedia, 2023)
Physical frailty is a clinical syndrome associated with deterioration of health, both physical and cognitive, in older adults. The main consequences are difficulties in performing activities of daily living, disability, hospitalization, co-morbidity with other pathologies and increased mortality. The main objective of this study was to test the influence of physical frailty on language in older adults without cognitive impairment. In addition, test the possible relationship between language and the level of autonomy through performance in instrumental activities of daily living will. Participants were 48 elderly people aged 65 years and older (7 men and 41 women) without pathological cognitive impairment. The mean age was 75,19 years (range 65-95). The variables assessed were physical frailty, presence of comorbid pathologies, educational level, ability to perform basic and instrumental activities of daily living, and linguistic performance. The results showed a positive association between age and physical frailty, and a negative association with the educational level of the participants. On the other hand, people with physical frailty had lower language performance than non-fragile people. An association was also found between language performance and instrumental activities of daily living. Therefore, to reverse or mitigate the negative effects associated with physical frailty syndrome, the design and implementation of interventions focused on the stimulation of cognitive and language skills would be useful.